Metal Halide Perovskites for Red‐Emission Light‐Emitting Diodes. Issue 10 (30th June 2022) - Wei, Keyu; Liang, Bing; Sun, Changjiu; Jiang, Yuanzhi; Yuan, Mingjian
Abstract : Metal halide perovskites (MHPs) exhibit remarkable optoelectronic properties, thus attracting widespread attention. Over the last several years, the external quantum efficiencies of perovskite light‐emitting diodes (PeLEDs) have exceeded 20%. Despite great progresses have been made, it remains challenging to realize high performance and stable PeLEDs. Especially, red‐emission PeLEDs still cannot meet the requirement of Rec. 2100 standard. Understanding the relationship between perovskite structure and their photophysical properties will greatly facilitate the development of PeLEDs. In this review, the structural and photophysical properties of MHPs are summarized, emphasizing three archetypes (CsPbI3, FAPbI3, and MAPbI3 ) of perovskites for red emission. Based on the fundamental characteristics, the recently emerged optical property modulation for obtaining high‐quality red‐emission perovskite films is outlined. Then, the approaches to optimizing electronics property and extending the operational lifetime of red‐emission PeLEDs are summarized. Finally, an outlook on the future challenges and potential directions toward red‐emission PeLEDs is represented. Abstract : Metal halide perovskites have remarkable optoelectronic properties and attract extraordinary attention. Red‐emission perovskite light‐emitting diodes (PeLEDs) still cannot meet the National Television System Committee standard. In this review, the recent progress and challenges on high‐performance pure red emitters are summarized. It is hoped that this review can provide a perspective for researchers to promote the PeLEDs commercialization.